Solution for Post-Mining Sites: Thermo-Economic Analysis of a Large-Scale Integrated Energy Storage System - Jakub Ochmann; Michał Jurczyk; Krzysztof Rusin; Sebastian Rulik; Łukasz Bartela; Wojciech Uchman (Energies, 2024)
The intensive development of renewable energy sources and the decreasing efficiency of conventional energy sources are reducing the flexibility of the electric power system. It becomes necessary to develop energy storage systems that allow reducing the differences between generation and energy demand. This article presents a multivariant analysis of an adiabatic compressed air energy storage system. The system uses a post-mining shaft as a reservoir of compressed air and also as a location for the development of a heat storage tank. Consideration was given to the length of the discharge stage, which directly affects the capital expenditure and operating schedule of the system. The basis for the analyses was the in-house numerical model, which takes into account the variability of air parameters during system operation. The numerical model also includes calculations of Thermal Energy Storage’s transient performance. The energy efficiency of the system operating on a daily cycle varies from 67.9% to 70.3%. Various mechanisms for economic support of energy storage systems were analyzed. The levelized cost of storage varies, depending on the variant, from 75.86 EUR/MWh for the most favorable case to 223.24 EUR/MWh for the least favorable case.